Soft Skills Development among EFL Students at Batna-2 University: Knowledge and Skills beyond Language Learning. - سعيدوني خولة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2022)
Teaching in the 21st century is a huge challenge to make good students with skills and expertise. This entails higher education institutions to cope with all the changes that occur within the different dimensions of life. To keep up with the development of science, technology, and the demands of globalization, high-level soft skills are needed for a successful life and career for students. Actually, there is a need to cultivate the soft skills that are crucial for personal growth, social interaction, and occupation success. In this regard, it is important for English as a foreign language (EFL) learners to develop both language hard skills and soft skills to engage effectively and successfully in their future careers. The aim of the current research is to find out whether the implemented activities in EFL classes support the development of soft skills. It also targets to explore the usefulness of soft skills for future career and professional development. Accordingly, the present paper employs a quantitative method of research. To reach the study aims, the needed data were collected using a survey questionnaire which was randomly administered to 90 Master two students. The findings of the study deliver significant results concerning soft skills development and offer some practical suggestions regarding soft skill inclusion in the EFL classroom.